A Multidimensional Assessment of Spouted-bed Roasted Almonds for Mitigating Acrylamide Formation While Enhancing Sensory and Functional Attributes - Puspantari, Widya; Yohanes, Heryoki; Astin, Eko Pratama; Hartono, Lusiana Kresnawati; Alfa, Mohamad Nafila; Komariyah, Kokom; Atmaji, Gigih; Pramono, Edi Priyo; Widodo, Wahju Eko; Setianto, Wahyu Bahari (Science and Technology Indonesia, 2025)
Almonds (Prunus dulcis) are widely valued for their nutritional composition and sensory properties, and roasting is commonly applied to enhance their flavor and extend their shelf life. However, thermal processing can degrade bioactive compounds and promote acrylamide formation. This study examined the effects of spouted-bed fluidization roasting at temperatures ranging from 150 to 180 °C for 5 to 7 min on acrylamide levels, antioxidant activity, physicochemical characteristics, and sensory profiles of almonds. The analytical methods included texture analysis, ultra-performance liquid chromatography (UPLC), colorimetry, Fourier-transform infrared spectroscopy (FTIR), and descriptive sensory evaluation. Acrylamide concentrations ranged from undetectable levels (<40 ppb) at 150 °C for 5 min to 1,672 ppb at 180 °C for 7 min. Total phenolic content increased at higher roasting temperatures (170–180 °C), reaching up to 0.90mg GAE/g, while antioxidant activity decreased from 0.51MBHA/g in raw almonds to 0.15–0.37MBHA/g in roasted samples. Roasting also reduced the moisture content (from 5.38% to 1.09%) and fracturability (from 102.39N to 71.81N), increased the browning intensity (BI: 42.13 to 30.77), and altered the FTIR spectra, indicating the formation of esters and carboxylic acids via Maillard reactions. Sensory evaluation showed that higher temperatures enhanced crispiness and aroma, but also increased bitterness and burnt characteristics. Overall, spouted-bed roasting at 160–170°C for 5–7 min minimized acrylamide formation while maintaining favorable sensory quality and preserving phenolic compounds. These results provide a basis for optimizing almond roasting parameters to improve safety and nutritional retention.